A study of cardiac and ciliary activity - Milton, A (1959)
Certain tissues have long been recognized to exhibit apparently normal movements when isolated from the body. Originally this was attributed to the presence of nervous tissue, but Gaskell and Engelmann towards the end of the nineteenth century established that cardiac muscle possessed the power of spontaneous rhythmic activity. It is now generally accepted that the heart beat is myogenic and not neurogenic in origin. Ciliary movement has always been regarded as autonomous and in 1924 Gray drew attention to the fact that the behaviour of cilia wider various conditions was similar to that of cardiac muscle. The natural occurrence and intense biological activity of the catechol amines and acetylcholine led to several workers to suggest that they might act as 'local hormones' controlling tissue activity at the site of production. Evidence has accumulated that acetylcholine, in addition to its function as a nervous transmitter, is responsible for the maintenance of spontaneous tissue movements. In 1952, Kordik, Bülbring and Burn made a comprehensive stody of the control of the ciliary activity on the epithelium which lined the frog's oesophagus and the rabbit's trachea. They reported the presence of the enzymes concerned with the synthesis and breakdown of acetylcholine, and they demonstrated that both acetylcholine and eserine in low concentrations stimulated activity, whereas in high concentrations these same drugs depressed the activity. Both atropine and tubocurarine were found to depress the activity. Recently Hill (1957) reported that she had been unable to repeat the observations of Kordik et al. on acetylcholine and tubocurarine, and she suggested that the previous re suite were due to artefacts arising out of the experimental procedure. As the earlier authors had stated that as a result of their observations they considered the ciliary activity to be controlled by acetylcholine it was thought necessary to undertake further experiments on the effect of tubocurarine and acetylcholine, and to try to account for the differences in the results obtained by Kordik et al. and those obtained by Hill. A preparation of the frog's oesophagus was a very strict experimental procedure was adhered to to avoid the possibility of artefacts arising. Under such conditions it was found that when the membrane was bathed with a bicarbonate Ringer's solution tubocurarine in a concentration of 10-6 g/ml caused a marked decrease in activity and acetylcholine in a concentration of 10-6 g/ml a marked increase. These results thus confirmed the previous findings of Kordik et al. On reinvestigating the methods which Hill had used it was noticed that in the majority of her experiments the membrane had been bathed with a Ringer's solution buffered with phosphate. Experiments were, therefore, carried out using this Ringer's solution to bathe the membrane and it was found that tubocurarine was in fact without significant effect. Further experiments showed that on the same preparation tubocurarine was without effect in the phosphate Ringer, and then caused a decrease in activity when the Ringer was changed to one containing bicarbonate instead of phosphate. Experiments showed that the effect was not due to changes in pH, but was probably due to a reduction in Ca++ ions caused by the complexing of these ions with the phosphate. Further experiments were carried out on a ciliated epithelium by Bülbring, Burn and Shelley in 1953 using the gill plates of Mytilus edulis, an example of a nerve free tissue. They measured both the force and the rate of the ciliary beat and observed the effect of acetylcholine, eserine, atropine and tubocurarine on these two activities. They concluded from their results that these cilia were also controlled by acetylcholine. They were able to demonstrate the presence of a true cholinesterase in the tissue, but the one weak link in their chain of evidence concerned the formation of acetylcholine. Though they found quite large amounts of acetylcholine in the gill plates they were only able to find a very low choline acetylase activity which would have been quite unable to maintain the high tissue level of acetylcholine. The choline acetylase activity of the gill plates has now been reinvestigated. By the use of more accurate and reliable methods a far higher activity has been found. A partially purified preparation of the enzyme showed a twenty fold increase in activity over that previously observed. The production of acetylcholine was measured over a wide range of temperature. It was found that a steady rate of production occurred over the normal experimental temperature range. The experiments of Bülbring et al. were carried out at 37°C and it was found that at this temperature the rate of synthesis was beginning to fall. Further experiments showed that whereas the enzyme was fairly stable at 20°C it was rapidly inactivated at 37°C. Gosselin (1959) has recently reported that both 5-hydroxytryptamine and 5-hydroxytryptophan stimulated the ciliary activity on the gill plates of Mytilus. He also reported the presence of a 5-hydroxytryptophan decarboxylase. As Bleschko and Hope (1957) failed to detect any amine oxidase activity in the gill plates it was decided to repeat their observations using 5-hydroxytryptamine as a substrate since this had not previously been used. The results showed that homogenates of Mytilus gill plates were able to oxidize 5-hydroxytryptamine but not tryptamine, tyramine or β-phenylethylamine. The reaction was not affected by Mersilid, a potent amine oxidase inhibitor, but was completely stopped by cyanide. These observations suggested that the enzyme was not an amine oxidase but a phenolase. Further to this idea it was found that 5-hydroxytryptophan was also oxidized. Experiments on the choline acetylase system and the synthesis of acetylcholine by acetone-dried powders prepared from rabbit atria were carried out in 1949 by Bülbring and Burn. They found that acetylcholine could be synthesized by the acetone powders in the presence of adenosinetriphosphate, citrate and 'boiled brain activator.' They observed that if acetylcholine was added to the reagents at the beginning of the experiment a decreased rate of synthesis resulted. They carried out further experiments in which they used acetone-dried powders which had been prepared from rabbit atria which had ceased to beat after being suspended in an isolated organ bath for many hours. They found that these powders were only capable of synthesizing acetylcholine in very small amounts, and when acetylcholine was added at the start of the experiment an increase in the synthetic rate was observed. A further observation made by Bülbring and Burn was that if small amounts of acetylcholine were added to a bath containing an atria which had ceased to beat, then the beat was often restarted. A sequel to this observation was made by Burn and Rand (1958) who showed that if a rabbit atria preparation with the vagi intact was cooled until the beat stopped, then stimulation of the vagi restarted the beat. The experiments now carried out were designed to repeat the observations of Bülbring and Burn using more modern techniques and to attempt to explain the unusual observations that under some conditions acetylcholine depressed, and under other conditions augmented the rate of synthesis. Experiments were also carried out to measure the acetylcholine content of normal atria, and atria which had ceased to beat from exhaustion. Observations were made on the effect of temperature on the rate of synthesis of acetylcholine, and particular attention was paid to that temperature range at which atria ceased to beat when they were cooled. The results obtained showed that the synthesis of acetylcholine was dependent on the availability of acetyl co-enzyme A. This emphasized the point that in any studies on choline acetylase it is essential that the availability of acetyl co-enzyme A does not become rate limiting. When acetylcholine was added to an incubation fully saturated with acetyl co-enzyme A no significant effect was observed. Further experiments showed, however, that if the acetyl co-enzyme A concentration was reduced then the addition of acetylcholine now caused a decrease in synthesis. Acetone-dried powders from exhausted atria were shown to have the same choline acetylase activity as acetone-dried powders from normal atria, and the addition of acetylcholine to the incubation mixture caused inhibition when the acetyl co-enzyme A concentration was low. The aceto-co-A-kinase activity of acetone powders from normal and exhausted atria was measured. The activity in the exhausted atria was found to be only 35% of the normal. This was thought to account for the low rate of synthesis observed by Bülbring and Burn with exhausted atria as they had relied upon this enzyme to catalyse the formation of acetyl co-enzyme A. Experiments were carried out in which the aceto-co-A-kinase present in the exhausted atria was relied upon to catalyse the formation of acetyl co-enzyme A, the results showed only a very low rate of synthesis. Under these conditions the addition of acetylcholine to the incubation mixture resulted in an increased synthesis. If the reaction mixture was supplemented with aceto-co-A-kinase a greater rate of synthesis was observed and now the addition of acetylcholine caused a decrease in synthesis. Estimations of the acetylcholine content of both normal and exhausted atria were made and the results indicated a 50% reduction in exhausted atria. Experiments on the choline acetylase activity over a wide range of temperature showed that the activity dropped very rapidly below 20°C in the range where atria stopped beating when they were cooled. Experiments were carried out on rabbit hearts to record the incidence of ventricular fibrillation induced electrically and the relationship between fibrillation, the composition of the perfusing fluid and the temperature. Armitage, Burn and Gunning (1957) and Kärki (1958) made observations on isolated rabbit hearts perfused using a modified Langendorff apparatus. They induced fibrillation electrically and noted whether the fibrillation continued or whether normal rhythm was restored after the cessation of the electrical stimulus. They recorded the percentage of hearts which remained fibrillating at given ionic concentrations of the perfusing fluid. They showed that a reduction in the K+ ion, and in the Na+ ion concentration favoured fibrillation, whereas a decrease in the Ca++ ion concentration made fibrillation less likely. The resulting curves plotting percentage fibrillation against ionic composition showed one or two unusual peaks especially when the Ca++ ion concentration was varied. In 1958 Goodford found that hearts which remained fibrillating at 37°C would often revert to a normal rhythm when cooled to 32°C, and he suggested that at 37°C, which was the temperature used by the previous workers, the heart was in a state of partial anoxia. Observations have now been made on the persistence of fibrillation at 32°C and 27°C. The results show the same trend as previously found, but the results show a more rational appearance. The results are discussed with a view to the fact that anoxia will affect both the length of the refractory period, and the rate of rise of the action potential.